Analysis of human blood plasma and hen egg white by chiroptical spectroscopic methods (ECD, VCD, ROA) - Synytsya, Alla; Judexová, Miluše; Hrubý, Tomáš; Tatarkovič, Michal; Miškovičová, Michaela; Petruželka, Luboš; Setnička, Vladimír (Analytical and bioanalytical chemistry, 2013)
Chiroptical methods are widely used in structural and conformational analyses of biopolymers. The application of these methods to investigations of biofluids would provide new avenues for the molecular diagnosis of protein-misfolding diseases. In this work, samples of human blood plasma and hen egg white were analyzed using a combination of conventional and chiroptical methods: ultraviolet absorption/electronic circular dichroism (UV/ECD), Fourier transform infrared absorption/vibrational circular dichroism (FTIR/VCD), and Raman scattering/Raman optical activity (Raman/ROA). For comparison, the main components of these substances--human serum albumin (HSA) and ovalbumin (Ova)--were also analyzed by these methods. The ultraviolet region of the ECD spectrum was analyzed using the CDNN CD software package to evaluate the secondary structures of the proteins. The UV/ECD, FTIR/VCD, and Raman/ROA spectra of the substances were quite similar to those of the corresponding major proteins, while some differences were also detected and explained. The conclusions drawn from the FTIR/VCD and Raman/ROA data were in good agreement with the secondary structures calculated from ECD. The results obtained in this work demonstrate that the chiroptical methods used here can be applied to analyze not only pure protein solutions but also more complex systems, such as biological fluids.
Keywords: sekundární struktura proteinů; Spectrum Analysis, Raman; cirkulární dichroismus; spektroskopie infračervená s Fourierovou transformací; krevní proteiny; Stereoisomerism; Blood Proteins; sérový albumin; Spectrophotometry, Ultraviolet; Serum Albumin; Spectroscopy, Fourier Transform Infrared; stereoizomerie; Protein Structure, Secondary; zvířata; Humans; Circular Dichroism; Software; Egg White; vaječný bílek; software; spektrofotometrie ultrafialová; aminokyseliny; Ramanova spektroskopie; lidé; Amino Acids; Animals